2015
DOI: 10.1523/jneurosci.2277-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Contributions of Ventromedial and Dorsolateral Subregions of the Human Substantia Nigra to Appetitive and Aversive Learning

Abstract: The role of neurons in the substantia nigra (SN) and ventral tegmental area (VTA) of the midbrain in contributing to the elicitation of reward prediction errors during appetitive learning has been well established. Less is known about the differential contribution of these midbrain regions to appetitive versus aversive learning, especially in humans. Here we scanned human participants with high-resolution fMRI focused on the SN and VTA while they participated in a sequential Pavlovian conditioning paradigm inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(104 citation statements)
references
References 53 publications
6
86
0
Order By: Relevance
“…Here we demonstrate a segregation between effort and reward learning within SN/VTA across the domains of task activation, functional connectivity, and gray matter density. In SN/VTA, a dorsomedial encoding of reward PEs, and a ventrolateral encoding of effort PEs, extends previous studies on SN/VTA subregions (56,57,67,68) by demonstrating that this segregation has functional implications that are exploited during multiattribute learning. In contrast to previous studies on SN/VTA substructures (56, 67-69), we performed whole-brain imaging, which allowed us to investigate the precise interactions between dopaminergic midbrain and striatal/ cortical areas.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Here we demonstrate a segregation between effort and reward learning within SN/VTA across the domains of task activation, functional connectivity, and gray matter density. In SN/VTA, a dorsomedial encoding of reward PEs, and a ventrolateral encoding of effort PEs, extends previous studies on SN/VTA subregions (56,57,67,68) by demonstrating that this segregation has functional implications that are exploited during multiattribute learning. In contrast to previous studies on SN/VTA substructures (56, 67-69), we performed whole-brain imaging, which allowed us to investigate the precise interactions between dopaminergic midbrain and striatal/ cortical areas.…”
Section: Discussionsupporting
confidence: 81%
“…Although dopaminergic activity cannot be assessed directly using fMRI, both effort and reward PEs were evident in segregated regions of dopaminergic-rich midbrain, and where an effective connectivity analysis indicated a directional influence from SN/VTA toward subcortical (reward PE) and cortical (effort PE) targets via ascending mesolimbic and mesocortical pathways, respectively. Dopaminergic midbrain is thought to comprise several distinct dopaminergic populations that have dissociable functions (54,56,67,68). Here we demonstrate a segregation between effort and reward learning within SN/VTA across the domains of task activation, functional connectivity, and gray matter density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence indicates that reward-related prediction errors also play a role in learning in humans. Numerous fMRI studies have reported correlations between RPE signals from RL models and activity in the striatum and midbrain nuclei known to contain dopaminergic neurons during Pavlovian and instrumental learning paradigms (D’Ardenne et al 2008, O’Doherty 2004, O’Doherty et al 2003b,Pauli et al 2015, Wittmann et al 2005). …”
Section: Neurocomputational Substratesmentioning
confidence: 99%
“…Given a suitable experimental design, this tendency might correspond to a lower fitted temperature parameter in a reinforcement learning model, which increases the probability that reinforced actions are repeated. Since key quantities in reinforcement learning models have well-established neural correlates (4649), measuring them in neuroimaging experiments could be an effective way to detect anxiety-related differences in neural activation [for a study addressing state anxiety, see Ref. (50)].…”
Section: Computational Backgroundmentioning
confidence: 99%